2023
DOI: 10.1002/btpr.3343
|View full text |Cite
|
Sign up to set email alerts
|

Analytical characterization of host‐cell‐protein‐rich aggregates in monoclonal antibody solutions

Abstract: Host‐cell proteins (HCPs) and high molecular weight (HMW) species have historically been treated as independent classes of impurities in the downstream processing of monoclonal antibodies (mAbs), but recent indications suggest that they may be partially linked. We have explored this connection with a shotgun proteomic analysis of HMW impurities that were isolated from harvest cell culture fluid (HCCF) and protein A eluate using size‐exclusion chromatography (SEC). As part of the proteomic analysis, a cross‐dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Several clusters detected also in the current work could be recovered, demonstrating the comparability between different data sets (Supplementary information Figure S3). In addition, some of these functional associations could initiate HCP aggregation, potentially promoting their co-purification, as suggested by recent studies (Herman et al, 2023a(Herman et al, , 2023bOh, Becker, et al, 2023).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Several clusters detected also in the current work could be recovered, demonstrating the comparability between different data sets (Supplementary information Figure S3). In addition, some of these functional associations could initiate HCP aggregation, potentially promoting their co-purification, as suggested by recent studies (Herman et al, 2023a(Herman et al, , 2023bOh, Becker, et al, 2023).…”
Section: Discussionmentioning
confidence: 86%
“…During the low pH elution, a subset of HCPs leach from the heteroaggregates, while the chromatin structure remains bound to the resin (Gagnon, Nian, Lee, et al, 2014). Apart from chromatin-derived aggregates, recent studies suggested that HCP aggregates detected in HCCF may also promote the persistence of HCPs during protein A chromatography (Herman et al, 2023a(Herman et al, , 2023bOh, Becker, et al, 2023). Most likely, several mechanisms are at play leading to the observed HCP co-purification.…”
mentioning
confidence: 99%
“…The measurements and their interpretation are discussed in Section 3.2.2, but an additional factor to be considered in the analysis is the physical form of the HCPs; specifically, HCPs that are incorporated in aggregate particles may not be accessible for binding to immobilized mAbs. To that end, we first discuss results of fractionating the null HCCF using size-exclusion chromatography (SEC).3.2.1 | Size-based characterization of HCPs in null HCCFThree fractions were collected from the null HCCF by size-exclusion chromatography (SEC)-a larger aggregate fraction, a smaller aggregate fraction, and the HCP main fraction; the larger and smaller aggregate fractions have been reported to be in size ranges of approximately 70-450 nm and 20-100 nm, respectively, by dynamic light scattering (DLS)(Gagnon, Nian, Lee, et al, 2014) but <100 nm in a subsequent study on different samples(Herman et al, 2023a). Although the sizes of the aggregate fractions from the samples in this study were not measured, the SEC methods and the collection windows for the fractions used here were comparable to those used in the previous studies.…”
mentioning
confidence: 99%